2021
DOI: 10.5222/tp.2021.65375
|View full text |Cite
|
Sign up to set email alerts
|

Age at Onset of Menarche and Puberty of Girls in Aydin Region and the Factors Affecting Them

Abstract: INTRODUCTION: In this study, we aimed to determine the range of mean age at onset of menarche (AOM) and puberty (AOP) of girls living in Aydin province and to determine the factors affecting the onset age of menarche. METHODS: A total of 1891 girls aged between 8 and 16 years attending primary, secondary and high schools in Aydin province were planned to be included in the study. A questionnaire that was prepared in line with the literature was delivered to the parents in a closed envelope. The subjects who ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previous studies reporting AAM in the various regions of Turkey also showed an ongoing decline in the menarcheal age since 1970s ( Figure 2 ) ( 10 , 12 , 13 , 14 , 15 , 16 , 17 ).…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…Previous studies reporting AAM in the various regions of Turkey also showed an ongoing decline in the menarcheal age since 1970s ( Figure 2 ) ( 10 , 12 , 13 , 14 , 15 , 16 , 17 ).…”
Section: Resultsmentioning
confidence: 65%
“…A similar discrepancy in the effect of parental education on AAM was also observed in studies from Turkey. Ataş Aslan and Ünüvar et al ( 17 ) found that LES was associated with earlier menarcheal age but this was not supported by Ersoy et al ( 14 ). We have found that higher maternal education was associated with earlier onset of menarche, as shown in some previous studies ( 23 , 26 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It indicated that most of them were within the range of regular menarche age. According to previous research, most females experienced menarche between 10 and 14 years old (Ravi et al, 2020;Aslan and Ünüvar, 2021;Nuraida et al, 2023).…”
Section: Discussionmentioning
confidence: 93%